EFFECTS OF COMPETITIVE STRATEGIES ON FINANCIAL PERFORMANCE IN THE DETERGENTS MANUFACTURING INDUSTRY IN KENYA - Waringo, Joshua; Muturi, Professor Willy (European Journal of Business and Strategic Management, 2018)
Purpose: The main purpose of this study was to determine the effects of competitive strategies on financial performance in detergent manufacturing industry in Kenya.. Methodology: The research design was a survey. Simple random sampling method was applied. A questionnaire was used to collect data. The population in this study was the 60 detergent manufacturing firms in Nairobi. Respondents involved were directors and finance managers in these factories. The study used questionnaires to collect the required data. Descriptive statistics was used mainly to summarize the data. SPSS was used for analysing complex data. The descriptive analysis involved the use cross tabulation and frequency distribution tables. Regression and correlation analysis were used to establish the relationship between the independent and dependent variables. Results: From the findings it was found that majority of the companies are constantly looking to adopt new technologies in their firm and that they are constantly looking to improve their sourcing processes. The findings also showed that most companies have measurable goals for achieving their marketing and sales objectives. Correlation test showed that there is a positive correlation between all the predictors (innovation & technology strategy, market strategy, operational excellence strategy, sustainability strategy) and financial performance of detergent manufacturing companies. Regression analysis showed R square to be 0.687, this indicated that innovation & technology strategy, market strategy, operational excellence strategy, sustainability strategy accounts for 68.7% of financial performance of detergent manufacturing companies. Statistically, the overall relationship was very significant with significant value, P value = 0.000, (P < 0.05). Policy recommendation: The study recommended that detergent manufacturing firms should adopt sustainability strategy as a non-generic strategy, in addition to the other strategies adopted. It also needs to improve or employ innovation/technology strategy as a key strategy